Twenty years later: Oral health‐related quality of life and standard of treatment in patients with chronic periodontitis. Issue 4 (20th November 2018) - El Sayed, Nihad; Baeumer, Amelie; El Sayed, Shirin; Wieland, Lars; Weber, Dorothea; Eickholz, Peter; Pretzl, Bernadette
Abstract: Background: To assess oral health‐related quality of life (OHRQoL) after long‐term (20 years) periodontal treatment in patients with chronic periodontitis (ChP) and to compare it with the current clinical outcome and oral health status. Methods: Twenty years after therapy, 63 patients were reexamined. The dental and periodontal status and OHRQoL using the Oral Health Impact Profile‐G49 (OHIP‐G49) were assessed. Descriptive statistics, correlation analysis, and tests for differences were calculated. Results: Up to 75% of patients showed no probing depths > 5mm, bleeding on probing (BOP) ≤25%, no pain and satisfactory function. A comparatively low perceived oral impact of ChP was represented by an OHIP‐G49 overall score of 18.89 ± 21.66. The most common reported impairment was physical pain followed by "functional limitation." A correlation between oral quality standard and the OHIP‐G49 was limited to the physical pain subdomain. Conclusions: Satisfaction with oral status was perceived high by most patients treated for chronic periodontitis. A comparably high OHRQoL can be achieved and retained long‐term after periodontal treatment. The objective and subjective evaluation of oral health only correlated in the subscale "physical pain."